Aqueous solubility of tri-iso-amyl phosphate (TiAP) - Effect of acidity, temperature and metal ions. (January 2020) - Mishra, Satyabrata; Kumar, Mukesh; Pandey, N.K.
Abstract: In recent times, tri- iso -amyl phosphate (T i AP) has been emerged as an alternate solvent to the existing tri-butyl phosphate (TBP) mainly for the aqueous reprocessing of high Plutonium content fast reactor fuels adopting the conventional PUREX process. Little solubility of the solvent in aqueous phase during extraction can lead to complex issues in further operations especially during the evaporation of raffinate. In this context, the aqueous solubility of tri- iso -amyl phosphate (T i AP) in a wide range of nitric acid concentrations from 0 to 14 M has been determined at three different experimental temperatures 298, 313 and 328 K. Various process parameters such as aqueous phase acidity and presence of heavy metal ions which affect the solubility of solvent are also discussed.